Role of Hypertension in Aggravating Aβ Neuropathology of AD Type and Tau-MediatedMotor Impairment. (19th August 2009) - Díaz-Ruiz, C.; Wang, J.; Ksiezak-Reding, H.; Ho, L.; Qian, X.; Humala, N.; Thomas, S.; Martínez-Martín, P.; Pasinetti, G. M.
Abstract : Epidemiological evidence suggests that hypertension may accelerate the onset and progression of Alzheimer's disease (AD). In this study, we explored the role of hypertension in the neurodegenerative changes associated with Aβ and tau aggregation. We induced hypertension inAPP swe Tg2576 and P301L-tauTg mouse models. In Tg2576 mice, experimental hypertension was associated with a significant increase of the accumulation of Amyloid-β (Aβ ) peptides in brain tissue and a significant reduction of Aβ peptides in serum( P < .05 ) . These results indicate that hypertension may promote AD-type Aβ neuropathology in Tg2576. In P301L-tauTg mice we found that the presence of hypertension was significantly associated with aggravated motor function assessed by hindlimb extension test( P = .01 ) . These results suggest that hypertension may play a role in accelerating the progression of motor dysfunction associated with tau-related alterations. Our studies suggest that the management of blood pressure (BP) may alleviate AD-type Aβ neuropathology and neurological disorders associated with abnormal tau metabolism.